3.3k views
4 votes
The first three steps of completing the square to solve the quadratic equation x² + 4x - 6 = 0, are

shown below.
Step 1: x2 + 4x = 6
Step 2: x2 + 4x + 4 = 6 + 4
Step 3: (x + 2)2 = 10
What are the next 3 steps?

User Alex Eagle
by
6.0k points

1 Answer

0 votes

Answer:

The next 3 steps are

Step 4:
(x+2)=\pm √(10)

Step 5:
x=-2\pm √(10)

Step 6:
x=-2+√(10)\ or\x=-2-√(10)

Explanation:

Given:

Quadratic Equation is

x² + 4x - 6 = 0

To Find:

x = ?

Solution:

Step 1: x2 + 4x = 6

Step 2: x2 + 4x + 4 = 6 + 4

Step 3: (x + 2)2 = 10

Step 4:
(x+2)=\pm √(10)

Step 5:
x=-2\pm √(10)

Step 6:
x=-2+√(10)\ or\x=-2-√(10)

User Brian Cragun
by
6.3k points